2010
DOI: 10.1007/s00340-010-4086-7
|View full text |Cite
|
Sign up to set email alerts
|

Two-color photoionization of calcium using SHG and LED light

Abstract: We present a photoionization method to load single 40 Ca ions in a linear Paul trap from an atomic beam. Neutral Ca I atoms are resonantly excited from the ground state to the intermediate 4s4p 1 P 1 -level using coherent 423nm radiation produced by single-pass second harmonic generation in a periodically poled KTiOPO 4 crystal pumped with an 120mW extended cavity diode laser. Ionization is then attained with a high-power light emitting diode imaged to the trap center, using an appropriately designed optical s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Our experiment starts from the loading of 40 Ca + ions by two-stage photoionization 52 using a 423 nm laser for the 4 S 0 -4 P 1 transition of the calcium atoms, followed by the second excitation by a 380 nm light emitting diode. The trapped ions are Doppler cooled by a grating-stabilized 397 nm laser, with assistance of a grating-stabilized 866 nm laser for D 3/2 -state repumping 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Our experiment starts from the loading of 40 Ca + ions by two-stage photoionization 52 using a 423 nm laser for the 4 S 0 -4 P 1 transition of the calcium atoms, followed by the second excitation by a 380 nm light emitting diode. The trapped ions are Doppler cooled by a grating-stabilized 397 nm laser, with assistance of a grating-stabilized 866 nm laser for D 3/2 -state repumping 50 .…”
Section: Resultsmentioning
confidence: 99%
“…In the second photo-ionization step, an extremely broad (∼ 1 nm) transition involving an auto-ionizing state can be used, which can be driven with cheap, unstabilized (blue-ray) laser diodes [18]. In the case of Ca [19] and Ba [15], light-emitting diodes (LEDs) have also proved effective.…”
Section: Isomentioning
confidence: 99%
“…To our knowledge, up until now the methods of electron impact ionization [17][18][19] and photo-ionization [20][21][22][23][24][25][26][27][28][29][30][31] have been the universal methods for producing ions in an ion trap. The traditional method of electron impact ionization is an effective tool that was first used for the generation of ions decades ago.…”
Section: Introductionmentioning
confidence: 99%
“…Using photo-ionization to load a single calcium ion into a Paul trap was first demonstrated by Kjaergaard et al [21], who adopted the 4 s 2 1 S 0 -4s5p 1 P 1 transition at a wavelength of 272 nm for excitation far above the ionization limit. Later, Gulde et al [22] and Schuck et al [23] demonstrated another scheme with the 4 s 2 1 S 0 -4s4p 1 P 1 transition at 423 nm followed by excitation close to the continuum by ultraviolet radiation (from an LED) near 390 nm. Following the success of this transition, Lucas et al [24] and Tanaka et al [25,26] performed 40 Ca + loading as well as the rare isotopes of 43 Ca + , 46 Ca + and 48 Ca + .…”
Section: Introductionmentioning
confidence: 99%